Citra Jepang Sebagaimana Tercermin pada Tiga Novel Selepas Perang Kemerdekaan - Sunu Wasono (HISKI, 2007)
Even though the Japanese occupation of Indonesia only lasted for two and a half years, it has left a strong impression in the minds of Indonesians. This is visible in three Indonesian novels. This paper discusses the images of Japan as reflected in the three Indonesian novels published after the war for independence: Pulang, Kadarwati, dan Para Priyayi. In the analysis of the three novels, it becomes clear that the Japanese presence in Indonesia had caused terrible sufferings on all levels of the society.